2017
DOI: 10.3389/fpls.2017.01648
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic and Nucleosolic Calcium Signaling in Response to Osmotic and Salt Stresses Are Independent of Each Other in Roots of Arabidopsis Seedlings

Abstract: Calcium acts as a universal second messenger in both developmental processes and responses to environmental stresses. Previous research has shown that a number of stimuli can induce [Ca2+] increases in both the cytoplasm and nucleus in plants. However, the relationship between cytosolic and nucleosolic calcium signaling remains obscure. Here, we generated transgenic plants containing a fusion protein, comprising rat parvalbumin (PV) with either a nuclear export sequence (PV-NES) or a nuclear localization seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 63 publications
(77 reference statements)
3
35
0
Order By: Relevance
“…Moreover, The NaCl-induced nucleoplasmic Ca 2+ signal had a higher amplitude than the cytoplasmic Ca 2+ signal, which contrasts with the cold-induced Ca 2+ signal, smaller in amplitude. These results support the induction of nuclear Ca 2+ signals independently of the cytoplasmic Ca 2+ release, as implied by a recent study regarding the NaCl-induced cytoplasmic/nuclear Ca 2+ dynamics (Huang et al, 2017 ). Alternatively, the cytoplasmic Ca 2+ release might be contributing to the generation of the nuclear Ca 2+ signal either by diffusion or by triggering a Ca 2+ -induced Ca 2+ release mechanism at the nuclear envelope.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, The NaCl-induced nucleoplasmic Ca 2+ signal had a higher amplitude than the cytoplasmic Ca 2+ signal, which contrasts with the cold-induced Ca 2+ signal, smaller in amplitude. These results support the induction of nuclear Ca 2+ signals independently of the cytoplasmic Ca 2+ release, as implied by a recent study regarding the NaCl-induced cytoplasmic/nuclear Ca 2+ dynamics (Huang et al, 2017 ). Alternatively, the cytoplasmic Ca 2+ release might be contributing to the generation of the nuclear Ca 2+ signal either by diffusion or by triggering a Ca 2+ -induced Ca 2+ release mechanism at the nuclear envelope.…”
Section: Discussionsupporting
confidence: 91%
“…The results ( Figure 1G; Videos S1, S2, and S3) showed that salt stress triggered a rapid increase in [Ca 2+ ] cyt as indicated by changes in the FRET signals of YC3.6 in the root cells of wild-type YC3.6 plants. The maximal changes in FRET signals (DE app /E apprest ) of YC3.6 in the wild-type nearly reached 0.2, similar to previous studies (Huang et al, 2017). However, the maximal changes of YC3.6 signals almost reached 0.5-0.6 in sos2 and scabp8 mutants, indicating a significantly greater increase in [Ca 2+ ] cyt (Figures 1H and 1I).…”
Section: The Sos2 and Scabp8 Negatively Regulate Salt-induced Increassupporting
confidence: 88%
“…It is also used for the calibration of fluorescent Ca 2+ indicators in animal cells [ 138 ]. As an alternative to the chemical Ca 2+ buffers, one could also employ Ca 2+ binding proteins, such as parvalbumin to locally buffer cytoplasmic Ca 2+ signals [ 292 ]. In non-plant systems, optogenetic modulation of light-gated cation channels allows for very precise modulation of Ca 2+ entry [ 293 ].…”
Section: Inhibition Strategy 4: Inhibition Of Cam-based Ca mentioning
confidence: 99%